서양의 唐詩 번역 양상 고찰 ― 20세기 전반기 英譯 唐詩選集을 중심으로 - 최석원; Choi Seokwon (중국학보, 2023)
19세기 진행된 일련의 唐詩 英譯은 극히 일부분이거나 전문적이지 못하다는 한계를 노출하고 있는 데 반해 20세기 唐詩 英譯은 양적인 증가는 물론 唐詩 번역의 전문화가 이루어졌다고 할 만하다. 본고는 이렇듯 唐詩 英譯이 활발했던 20세기 전반기를 연구 대상으로 삼아 서양에서의 唐詩 읽기의 양상과 이에 대한 인식의 일면을 확인하는 데 목적을 두었다. 이를 위하여 20세기 초에 간행된 英譯 唐詩選本들의 문헌 상황에 대해 개괄하고 그중 지금껏 唐詩 번역의 영향력을 발휘하고 있는 관련 문헌 2종, Gems of Chinese Verse와 The Jade Mountain, A Chinese Anthology: Being Three Hundred Poems Of The Dang Dynasty 618-906에 대한 고찰을 진행하였다. 함께 唐詩 번역의 구체적인 사례 가운데에서도 고유명사에 대한 번역의 경향성을 통해 중국과 서양이 지닌 ‘시’에 대한 인식 차이의 일면을 확인하였다. English translation of 19 th -century Tang poems is exposing the limitations of being unprofessional. However, in the 20 th century, the English translation of Tang poems increased quantitatively, and the translation of Tang poems was specialized. The purpose of this paper was to identify aspects of Tang poetry reading in the West and aspects of perception of the Tang poetry, using the first half of the 20 th century as a research subject. To this end, I summarized the bibliography of the domain books published in the early 20 th century, and reviewed two related documents, Gems of China Verse, and The Jade Mountain, A Chinese Anthology: Being Three Hundred Poems Of The Dang Dynasty 618-906, which have been influential in translation at the time. In addition, one side of the difference in perception of "poetry" between China and the West was confirmed through the tendency of translation of proper nouns among Tang poetry translation.